368 Anatomy and White Matter Connections of the Orbitofrontal Gyrus. (August 2016) - Burks, Joshua Dee; Bonney, Phillip A.; Conner, Andrew K.P.; Glenn, Chad A.; Briggs, Robert G.; Boettcher, Lillian B.; O'Donoghue, Daniel L.; Wu, Dee H.; Sughrue, Michael Edward
Abstract : INTRODUCTION: The orbitofrontal cortex is understood to have a role in outcome evaluation and risk assessment, and is commonly involved by infiltrative tumors. A detailed understanding of the exact location and nature of associated white tracts could go far to prevent postoperative morbidity related to declining capacity. Through diffusion tensor imaging (DTI)-based fiber tracking validated by gross anatomical dissection as ground truth, we have characterized these connections based on relationships to other well-known structures. METHODS: Diffusion imaging from the Human Connectome Project for 10 healthy adult controls was used for tractography analysis. We evaluated the orbitofrontal cortex as a whole based on connectivity with other regions. All orbitofrontal cortex tracts were mapped in both hemispheres, and lateralization index was calculated with resultant tract volumes. Ten postmortem dissections were then performed using a modified Klingler technique to demonstrate the location of major tracts. RESULTS: We identified 3 major connections of the orbitofrontal cortex: a bundle to the thalamus and anterior cingulate gyrus passing inferior to the caudate and medial to the vertical fibers of the thalamic projections; a bundle to the brainstem traveling lateral to the caudate and medial to the internal capsule; and radiations to the parietal and occipital lobes traveling with the inferior fronto-occipital fasciculus. There was no significant lateralization for any of the tracts described. CONCLUSION: The orbitofrontal cortex is an important center for processing visual, spatial, and emotional information. Subtle differences in executive functioning following surgery for frontal lobe tumors may be better understood in the context of the fiber-bundle anatomy highlighted by this study.